2015
DOI: 10.1080/23303131.2015.1031416
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Turnover in Nonprofit Human Service Organizations: The Impact of High Performance Work Practices

Abstract: Voluntary turnover in nonprofits can present a significant cost, reducing the performance of a nonprofit and challenging its sustainability over time. This study examines voluntary turnover in a sample of human service (HS) nonprofit organizations in eight states, exploring the relationship between the implementation of high performance work practices (HPWP) and voluntary turnover. The findings demonstrate that certain HPWPs, including onboarding, leadership development, compensation, and employee relations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 129 publications
2
82
0
2
Order By: Relevance
“…We include a measure of the priority the manager places on HR and a measure of how much the hospital works to create a common corporate culture among all employees as well as the manager's race and gender. We include a measure of employee turnover, as numerous studies have demonstrated the relationship between turnover and organizational performance (see Batt & Colvin, ; Gardner et al, ; Selden & Sowa, for a small sample of these studies). Turnover is measured by the following response from the CEO: “Our hospital has high clinical turnover.” In addition, resources can have a significant impact on the performance of nonprofits; this was particularly true during the time period in which this study was conducted (Boris, deLeon, Roeger, & Nikolova, ; Salamon, Geller, & Spence, ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We include a measure of the priority the manager places on HR and a measure of how much the hospital works to create a common corporate culture among all employees as well as the manager's race and gender. We include a measure of employee turnover, as numerous studies have demonstrated the relationship between turnover and organizational performance (see Batt & Colvin, ; Gardner et al, ; Selden & Sowa, for a small sample of these studies). Turnover is measured by the following response from the CEO: “Our hospital has high clinical turnover.” In addition, resources can have a significant impact on the performance of nonprofits; this was particularly true during the time period in which this study was conducted (Boris, deLeon, Roeger, & Nikolova, ; Salamon, Geller, & Spence, ).…”
Section: Methodsmentioning
confidence: 99%
“…For many nonprofits, one of their primary expenditures at the program level is their staff; while there is no one set figure for this, salaries can often be the largest portion of a nonprofit's budget. Effective HRM practices can ensure these expenditures are maximized to promote the most value (Akingbola, ; Pynes, ; Ridder et al, ; Ridder & McCandless, ; Selden & Sowa, ; Walk et al, ). In nonprofits providing direct services to clients, such as health and human service organizations, the worker–client interaction is one of the fundamental ways in which value is produced (Benjamin & Campbell, ; Hasenfeld, ; Sosin, ).…”
Section: Hrm and Nonprofit Performancementioning
confidence: 99%
See 2 more Smart Citations
“…However, most authors argue that a multidimensional approach is most appropriate since it captures a wider scope of organisational elements and presents a more accurate view of organisational effectiveness (Matthews 2011, Giti and Suhaida 2012, Selden and Sowa 2015.…”
Section: African Contextmentioning
confidence: 99%